Get It Fast, Pay It Later: Analysis of Paylater Features as A Support of The Generation Z Lifestyle - Fauza Husna (Department of Tadris IPS FITK IAIN Syekh Nurjati Cirebon, 2023)
ABSTRACTThe paylater feature is a new combination from the times. Currently, paylater is part of the transaction that is popular with many groups, one of which dominates is the younger generation. This transaction is considered practical because it is able to grant the wishes of its users quickly and with minimal obstacles. This study aims to analyze the existence of the paylater feature among Generation Z in fulfilling lifestyles in this modern era. The method used is a qualitative descriptive method or a method that is included in the type of literature research where the authors retrieve data through written data sources and other related sources. The concept of